2022
DOI: 10.1108/k-09-2021-0866
|View full text |Cite
|
Sign up to set email alerts
|

Digital inclusive finance, economic growth and innovative development

Abstract: PurposeThis paper aims to explore the impact of digital inclusive finance (DIF) on regional economic growth and innovation-driven development.Design/methodology/approachBased on the panel data of 31 provinces (autonomous regions and municipalities directly under the central government) in China from 2011 to 2018, this paper explores the impact of DIF on economic growth and innovative development.Findings(1) DIF has a direct positive effect on economic growth and innovative development; (2) there is significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…In addition, the development of digital inclusive finance can make farmers easy access to funds, bonds, stocks, investment opportunities, and core financial services, facilitate farmers' financial management, maintain or increase wealth, and increase farmers' willingness and ability to invest in upgrading the skill and education of human capital. Therefore, it can be concluded that DFI has a positive effect on rural human capital accumulation (Wang, He and Le, 2022) (Wang et al, 2022). This positive relationship becomes more significant and progressive with the development and application of digital inclusive finance in these areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the development of digital inclusive finance can make farmers easy access to funds, bonds, stocks, investment opportunities, and core financial services, facilitate farmers' financial management, maintain or increase wealth, and increase farmers' willingness and ability to invest in upgrading the skill and education of human capital. Therefore, it can be concluded that DFI has a positive effect on rural human capital accumulation (Wang, He and Le, 2022) (Wang et al, 2022). This positive relationship becomes more significant and progressive with the development and application of digital inclusive finance in these areas.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, it may help to develop the rural human capital and its accumulation by offering easy financial assistance to promote higher and technical education. Thirdly, it may affect the accumulation of rural human capital by giving more job opportunities and other sources of income to rural residents (Wang et al, 2022). An increase in income level will raise the propensity of the people to spend income on education and technical learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-term inadequate supply of traditional financial services makes enterprises face serious external financing constraints, which greatly weakens innovation ability (Cao et al, 2021). Compared with the exclusivity of traditional finance, digital finance expands the breadth and depth of financial services, reduces financial transaction costs, and improves the external financing environment of enterprises (Wang et al, 2022b). Convenient financing channels and low financing costs meet the capital needs of enterprises in production and operation, value chain reshaping .…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Therefore, digital inclusive finance has received wide attention from all walks of life. Academic research on digital inclusive finance has focused on the impact of digital inclusive finance on commercial banks' efficiency and commercial bank risk (Pazarbasioglu et al, 2020), innovation and entrepreneurship (Wang and Zhang, 2022), urban-rural income gap and inclusive growth (Yao and Ma, 2022), residential consumption (Li, 2021) and carbon emissions (Wang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Current research seldom discusses green finance and industrial technology innovation, instead focusing on the identification of the causal relationship between financial development and technology innovation. For example, finance development can provide an inexhaustible source of funds, ensure the continuity, and reduce the external risk impact of technology innovation (Irwan et al, 2021;Stefano et al, 2022;Wang W. J. et al, 2022). Technology innovation can significantly improve, accelerate, and stabilize the quality of finance development (Chi et al, 2021;Ge et al, 2022;Sun and Razzaq, 2022).…”
Section: Introductionmentioning
confidence: 99%